BANDUNG CITIZEN INTENTION TO PURCHASE ON CHOCOLATE BASED ON ITS’ PACKAGING GRAPHICAL ELEMENTS - Husna, Nabila; Hudrasyah, Herry (Journal of Business and Management, 2017)
Abstract.Background – Indonesia is the third largest cacao producer in the world. However, chocolate consumption inside the country is still low. Packaging is a reliable promotional strategy in the retail environment to attract customers. By using a combination of graphical elements, it may promote product appeal and may influence purchase intention. Methods - The graphical elements in this study are color, typography, graphical shapes, and images that become independent variable and purchase intention become dependent variable. 273 respondents who are domiciled in Bandung are obtained as primary data. To know the effect of independent variable   to   dependent   variable,   multiple   linear   regression   is   used.   Result  -   This   study   found   that simultaneously all independent variables are significantly influence dependent variables. Partially, however, the color variables have no significant effect on purchase intention, with the most influential variables are typography, followed by graphical shapes, image, and lasty color. Conclusion – A product information and brand name can be a point for customers to purchase chocolate with an appealing typography, support by a real product picture and a good composition. Color still can attract customer for brand recognition, giving a higher chance for chocolate to be purchased. Keywords: Chocolate, Packaging, Graphical Elements, Purchase Intention.